A counseling system to predict the study path for freshmen - Usha, Rowshni Tasneem; Parvez, Shiny Raisa; Sejuti, Fariha Sazid; Hossain, Maisha (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.